Analisis molekular gena apolipoprotein A-IV pada kelompok penderita dan bukan penderita penyakit jantung koroner=Molecular Analysis of Apolipoprotein A-IV Gene in Patients of Coronary Heart Disease and Norma I Individua - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT Coronary Heart Disease (CHD) is a multifactorial disease in which genetic factors may play some roles. Although the role of Apo A-IV remains to be established, it has been shown to function as an activator for LCAT (Lecithin -.cholesterol acyltransferase) and play a role in the removal process of excess cholesterol from the tissue by HDL [High Density Livoprotein). Therefore, Apo A-IV is one of the CHD risk factors. The Apo A-IV gene appears to be highly polymorphic at DNA level. Apo A-IV 2 alelle which is caused by mutation of codon 360 (Gin â His) has been shown to increase the individual susceptibility to CHD. This alelle was not found in the Japanese population (which was included to Northern Mongoloid), so it was suggested that it was unique to the Caucasian gene pool. The problem which would be studied in this work was on the molecular characteristic of Apo A-IV in the CHD patients and healthy group belong to the Javanese ecthnic group in Yogyakarta. The present study also learned the relationship between the molecular characteristic of Apo A-IV gene with the CHD incidence rate and with the plasma lipid profile on the CHD patients and healthy groups. The present study was intended to observe the molecular basic of Apo A-IV gene which was involved in CHD risk factor on Javanese etnic group as the constituent of Southern Mongoloid. The subjects of this study consisted of 20 CHD patients and 20 healthy subjects. The molecular analysis of the Apo A-IV gene was carried out by PCR-SSCP (Polymerase Chain Reaction - Single Strand Conformation Polymorphisms) method, and then continued by DNA sequencing analysis. The plasma lipid profile was determined by enzymatic colorimetric test. The result showed that there were two kinds of molecular form of Apo A-IV gene in both groups of Javanese ethnic group in Yogyakarta, i.e. Apo A-IV1/1 and Apo A-IV 1/x. Apo A-IV x alelle was a novel alelle which was caused by mutation in codon 344 (Gin -) His). Similar to that in the Japa-